Upaya Meningkatkan Aktivitas dan Prestasi Belajar Matematika Melalui Penerapan Model Pembelajaran Konstruktivisme dengan Pendekatan pemecahan Masalah pada Siswa Kelas IV SD Negeri 1 Apuan Tahun Pelajaran 2022/2023 - Suadra, I Made (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2023)
This research was motivated by the low activity and learning achievement in mathematics of class VI students at SD Negeri 1 Apuan, academic year 2022/2023. To overcome this problem, research was carried out by applying the constructivist learning model. This research aims to increase student activity and learning achievement at the school. By implementing classroom action research which was carried out in two cycles. Data about student learning activities was collected using observation sheets, while data on student learning achievement was collected using learning achievement tests. The results of this research indicate that there has been an increase in learning activities in class VI students at SD Negeri 1 Apuan. In the initial reflection, student learning activity was 1.52 which was classified as less active. In cycle I, there was an increase in the average score of student learning activities by 2.26, which was classified as quite active. Meanwhile, in cycle II the average score for student learning activities was 3.33, which was classified as active. The average score of student learning achievement in the initial reflection was 65.74. In cycle I the average score of student learning achievement increased to 72.61, while from cycle I to cycle II it increased by 8.48 to 81.09. It was concluded that the application of the constructivist learning model through a problem-solving approach could increase the activity and mathematics learning achievement of class VI students at SD Negeri 1 Apuan, academic year 2022/2023. From the results of this research, it is recommended that teachers apply this learning model so that the concepts and learning materials can be easily accepted and understood by students.